2016
DOI: 10.1371/journal.pone.0164767
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress following Injury in a Large Cohort of Thai Adults

Abstract: IntroductionInjury and psychological distress are public health priorities because of their high occurrence in the population. This study examines the longitudinal effects of injury characteristics on psychological distress.MethodsStudy participants were enrolled distance learning Thai adults (N = 42,785 at 2013 follow-up) residing nationwide. We analysed 2009 and 2013 data. Injury questions included injury prevalence, causes and levels of severity. Distress was measured using the standard Kessler-6. To assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
(30 reference statements)
0
4
2
Order By: Relevance
“…In this study, the number of patients having psychological distress was found to be higher than the previous studies for unintentional injury survivors in the United States, in which 3.7% and 5.3% of those reported moderate and severe levels of psychological distress, respectively [17]. Additionally, in a cohort study conducted with 87,151 distance learning students in Thailand, more than one-third of traffic-injury members were found to qualify for psychological treatment [16]. As all participants in this study were inpatients, receiving direct support from health professionals could be a reason for the lower level of distress.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In this study, the number of patients having psychological distress was found to be higher than the previous studies for unintentional injury survivors in the United States, in which 3.7% and 5.3% of those reported moderate and severe levels of psychological distress, respectively [17]. Additionally, in a cohort study conducted with 87,151 distance learning students in Thailand, more than one-third of traffic-injury members were found to qualify for psychological treatment [16]. As all participants in this study were inpatients, receiving direct support from health professionals could be a reason for the lower level of distress.…”
Section: Discussioncontrasting
confidence: 64%
“…Previous literature has established a link between injuries and psychological distress [8,13,16,17]. It can be seen that unintentional injuries (i.e., automobile crashes, industrial accidents, home accidents) not only increased the risk of psychological issues, but were also associated with illicit drug use, alcohol use, and violent behavior [9,10,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…There were no associations observed between injury severity (measured by NISS) and injury cause with distress at 12 years post-SIE, which was somewhat expected given that these factors were only associated with distress at 12 months post-SIE but not at 24 months in our cohort (Richardson et al 2021). In contrast, internationally, injury severity has been found to be associated with distress at 12 months (Kendrick et al 2017) and four years post-injury (Tran et al 2016) and sustained over a five-year period, once behavioural factors were controlled for (e.g. sleep and exercise) (Saunders et al 2012).…”
Section: Discussioncontrasting
confidence: 42%
“…Fewer studies (18%) were conducted in Asian, South American, African and Middle Eastern countries. Knowing that official crash data are not always available to the researcher and road authorities in developing countries (see, e.g., [11]), developing countries would benefit from using the self-reporting approach to conduct road safety studies so that the real safety situation of the country could be appropriately assessed to determine the crash causation factors, estimate underreporting, crash costs and reveal other effects (e.g., psychological distress after injury as studied by Tran et al [145]), and consequently improve their traffic situations. A WHO [7] reported, most of the traffic deaths (approximately 90%) occur in developing countries, where rapid economic growth in parallel with motorisation has led to traffic injuries, especially those involving VRUs (60-70%).…”
Section: Discussionmentioning
confidence: 99%
“…Various motivations were found to drive the studies on self-reporting of traffic crashes, such as safety evaluation [21,, investigation of crash causation factors [22,, determination of the number of crashes for a specific group (e.g., novice drivers, elderly) , estimation of underreporting [15,20,[132][133][134][135][136][137][138][139], calculation of crash costs [140] or other factors (e.g., to investigate the memory effect) [141][142][143][144][145]. However, all studies were conducted at the very least to understand and assess the traffic safety situation.…”
Section: Focus Of the Studiesmentioning
confidence: 99%